THE IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL TO IMPROVE THE FIRST GRADE STUDENTS’ MATHEMATICAL CONCEPT UNDERSTANDING AT SDN BABAKAN - Dinda Ayu Wulandari; Galih Dani Septiyan Rahayu (Sekolah Pascasarjana UPI, 2022)
This research is motivated by the low ability of grade 1 students in understanding math word problems. Math story problems are a form of math problems that contain aspects of the ability to read, reason, analyze, and find solutions. This study aims to describe the Problem Based Learning model assisted by snakes and ladders game media that can be implemented to solve problems related to the low ability of students to understand story problems. This research is a qualitative research using classroom action research methods. Data were collected using in-depth interviews, observation, documentation studies, and data were analyzed qualitatively descriptively. Researchers analyzed the data by means of data reduction, data presentation, and drawing conclusions and verification. This research was conducted in two cycles. The pre-cycle percentage based on the results of the researchers' observations was only 40% of students who scored above the KKM. These results have increased quite well after the implementation of PTK. Evidenced by the results of the average percentage of students’ understanding of mathematical concept in cycle I of 67% of students getting scores above the KKM. In cycle II there was an increase to 87% of students getting scores above the KKM. The data shows that students' understanding of mathematical concepts in mathematics subject matter of word problems has increased through the application of the Problem Based Learning model assisted by snakes and ladders game media.